The Influence of Plasma Composition on Mechanical Stresses in Substrate-Coating System; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Shanin S. A. Sergei Aleksandrovich (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen